Generation of Business Process Models for Object Life Cycle Compliance - Ryndina, Ksenia; Küster, Jochen; Gall, Harald (Proceedings of the BPM Demonstration Program (satellite event of the 5th International Conference on Business Process Management (BPM 2007)), Brisbane (Australia))

Smart Teams: Simulating Large Robotic Swarms in Vast Environments - Arens, Stephan; Buss, Alexander; Deck, Helena; Dynia, Miroslaw; Fischer, Matthias; Hagedorn, Holger; Isaak, Peter; Kutylowski, Jaroslaw; Meyer auf der Heide, Friedhelm; Nesterow, Viktor; Ogiermann, Adrian; Stobbe, Boris; et al. (Proceedings of the 4th International Symposium on Autonomous Minirobots for Research and Edutainment)
We consider the problem of exploring an unknown environment using a swarm of autonomous robots with collective behavior emerging from their local rules. Each robot has only a very restricted view on the environment which makes cooperation difficult. We introduce a software system which is capable of simulating a large number of such robots (e.g. 1000) on highly complex terrains with millions of obstacles. Its main purpose is to easily integrate and evaluate any kind of algorithm for controlling the robot behavior. The simulation may be observed in real-time via a visualization that displays both the individual and the collective progress of the robots. We present the system design, its main features and underlying concepts.

Reusable Architectural Decision Models for Enterprise Application Development - Zimmermann, Olaf; Gschwind, Thomas; Küster, Jochen; Leymann, Frank; Schuster, Nelly (Proceedings the conference on Quality of Software-Architectures (QoSA 2007), Medford, MA (USA))

"Modelchecking" - Eine Methode zur Verbesserung der Softwarequalität - Gehrke, Matthias; Güldali, Baris; Kindler, Ekkart

Investigation of multicast-based mobility support in all-IP cellular networks - Festag, Andreas; Karl, Holger; Wolisz, Adam (Wireless Communications and Mobile Computing)

WASP - Wirelessly Accessible Sensor Populations: A Project Overview - van der Stok, Peter; Karl, Holger; De Ambroggi, Fabio; Decotignie, JeanDominique; Siegemund, Frank; Lokhorst, Kees; Hellenschmidt, Michael (Constructing Ambient Intelligence - AmI 2007 Workshops Darmstadt, Germany, November 7-10, 2007 Revised Papers)

Outage probability analysis of cooperative transmission protocols without and with network coding: inter-user channels based comparison - H. Woldegebreal, Dereje; Valentin, Stefan; Karl, Holger (Proceedings of the 10th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2007, Chania, Crete Island, Greece, October 22-26, 2007)

Traffic-Aware Asymmetric Cooperation Diversity for Media Streaming in Wireless Networks - Valentin, Stefan; von Malm, Holger; Karl, Holger (Proceedings of the IEEE 18th International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC 2007, 3-7 September 2007, Athens, Greece)

Integrating multiuser dynamic OFDMA into IEEE 802.11a and prototyping it on a real-time software-defined radio testbed - S. Lichte, Hermann; Valentin, Stefan; Eitzen, Falk; Stege, Matthias; Unger, Carsten; Karl, Holger (3rd International ICST Conference on Testbeds and Research Infrastructures for the Development of Networks and Communities, TridentCom 2007, Orlando, Florida, USA, May 21-23 2007)

Finanzwirtschaftliche Analyse der schenkungsteuerlichen Zehnjahresregel - Kundisch, Dennis; Pfeiler, F.; Schiefele, V. (Steuer und Wirtschaft)

Customer Portfolio Management in E-Commerce – A Risk Management Perspective - Kundisch, Dennis; Sackmann, S.; Ruch, M. (INFORMS International Puerto Rico 2007 Meeting)

Außerbörslicher Emittentenhandel: Handelsplatzwahl von Online-Investoren - Kundisch, Dennis; Stuber, T. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Bank controlling using Basel II-data: Are internal approaches dispensable? - Kundisch, Dennis; Loehner, F.; Rudolph, D.; Steudner, M.; Weiss, C. (2007 Enterprise Risk Management Symposium Monograph)

Spezifizierung des Kano-Modells zur Messung von Kundenzufriedenheit - Buhl, H. U.; Kundisch, Dennis; Schackmann, N.; Renz, A. (Wirtschaftsinformatik 2007 - eOrganisation: Service-, Prozess-, Market-Engineering)

Feedbackgespräche: Überstrapaziert, missverstanden und bedeutungslos? Ganz im Gegenteil: Best Practise bei der Deutschen Bahn - Terlinde, P; Giardini, A; Kabst, Rüdiger; Halbach, J; Pelchrzim, H

Strategische Personalentwicklung: Wenn dem Bildungscontroller die Ziele fehlen - Giardini, A; Kabst, Rüdiger

Funktionale Äquivalente zur Personalplanung : Eine empirische Studie zur Personalplanung klein- und mittelständischer Unternehmen auf Basis des Cranet - Matiaske, W; Holtmann, D; Kabst, Rüdiger (Planung in kleinen und mittleren Unternehmen, Jahrbuch der KMU-Forschung und -Praxis 2007)

Leistungsbeurteilung und -vergütung in der privaten Wirtschaft und im öffentlichen Dienst: Eine vergleichende Betrachtung auf Basis des „Cranfield-Projects“ 1995-2005 - Giardini, A; Kabst, Rüdiger (Leistungsvergütung im Öffentlichen Dienst)

Preventing E-mail Spam: The Conceptualization and the Analysis of an Infrastructure Framework - Schryen, Guido
Spamming remains a form of Internet abuse, which burdens the Internet infrastructure, is generally regarded as an annoyance, and is said to cause a huge economic harm. Many technological, organizational, and legislative anti-spam measures have already been proposed and implemented, but have not led to any substantial decrease in the number of spam e-mails. We propose a scalable and flexible infrastructure framework that integrates several anti-spam measures and that features both a technological and an organizational facet. The key element of our infrastructure is a new organizational unit that reliably and transparently limits the number of e-mails that can be sent per day and per account. We also analyze the proposed framework in terms of its theoretical effectiveness, the required resources, and its limitations.
Keywords: Email; Infrastructure; Internet; Spam

Joint Venture Performance: A Meta-Analysis - Isidor, R; Hornung, F; Kabst, Rüdiger